EDIBLE FISH POWDER FROM DHOMA (SCIAENIDS SPP.) - SOLANKI, K K; DEVADASAN, K; VENKATARAMAN, R (Fishery Technology, 2017)
Edible fish powder of high protein content was prepared from Dhoma (Sciaenids) using different methods. A comparative account of the yield and quality of the products prepared by these methods is presented